Nitric Oxide Action in Abiotic Stress Responses in Plants 2015
DOI: 10.1007/978-3-319-17804-2_9
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide and UV-B Radiation

Abstract: Over the past few years, nitric oxide (NO) has emerged as a key player in plant adaptive/hypersensitive responses to abiotic (stress) factors, since the content of endogenously generated NO increases in adverse environmental conditions. This chapter addresses to the signalling events with the involvement of the reactive nitrogen species under ultraviolet-B (UV-B) exposure. Solar UV-B has long been recognized as merely deleterious environmental factor; however, rapidly increasing evidence indicates that it play… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 87 publications
(107 reference statements)
0
5
0
Order By: Relevance
“…As a linking regulator, the rice formin protein formin homology 5 (FH5) plays a critical role in determining plant morphology by regulating the dynamics of actin and the proper spatial organization of microtubules and microfilaments 26 . This finding implies that formin proteins act as upstream factors of actin filaments and microtubules and downstream factors of HY5 and NO 27 . There may also exist unknown factors that receive signals from UVR8/COP1/HY5 and regulate actin filaments, which may influence the rate of cell mitosis and seedling growth ( Fig.…”
Section: Discussionmentioning
confidence: 85%
“…As a linking regulator, the rice formin protein formin homology 5 (FH5) plays a critical role in determining plant morphology by regulating the dynamics of actin and the proper spatial organization of microtubules and microfilaments 26 . This finding implies that formin proteins act as upstream factors of actin filaments and microtubules and downstream factors of HY5 and NO 27 . There may also exist unknown factors that receive signals from UVR8/COP1/HY5 and regulate actin filaments, which may influence the rate of cell mitosis and seedling growth ( Fig.…”
Section: Discussionmentioning
confidence: 85%
“…Abiotic stresses provoke changes in NO levels directly or via ROS and hormonal mediation that, in turn, leads to activation of antioxidant enzymes expression and elimination of superoxide anions and lipid radicals ( Siddiqui et al, 2011 ). Nitric oxide synthase (NOS) activity was shown to be significantly increased by UV-B irradiation, suggesting that NO may act as a secondary messenger under UV-B irradiation ( Yemets et al, 2015 ). In plants, action of exogenous NO (namely, using SNP as a donor) under UV-B irradiation was shown to allow photosystem II protection and ROS scavenging ( Shi et al, 2005 ; Wang et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a number of reports provide evidence for the protective effects of NO in plants challenged with UV-B. These effects include UV-B mediated changes of NO synthase-like and nitrate reductase activity; protective action of exogenous NO donors; interrelation of NO and ROS signaling pathways; NO impact on the ROS scavenging system activity; and the role of NO in UV-B perception by plant cell (summarized in Yemets et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, there are no studies that link MET with NO in the response to high light stress, waterlogging and nutrient deficiency. However, different studies have shown that NO is involved in the tolerance to high light stress [124]. Kim et al (2010) demonstrated that NO was involved in the high light tolerance of maize (Zea mays L.) leaves of seedlings.…”
Section: General Roles Of Met In Abiotic Stress Tolerancementioning
confidence: 99%